A la Griba (Synagogue à Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Couseuse accroupie (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Couseuse assise (bleu et rose) (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Femme et enfant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Femme juive (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Femme portant l’enfant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Femme serrant son bel enfant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeune femme assise tenant son enfant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeune fille aveugle tenant son frère (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeune fille (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeune fille juive (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeune fille tenant son frère (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeune mariée aux gros yeux (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Jeunes hébreux lisant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Juive assise avec son enfant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Juive aux grains de blé assise et son enfant (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Liseur accroupi (La Griba, Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Nouvelle mariée juive (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Rachel (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
Publisher: Persée - Portail des revues scientifiques en SHS
Keywords: Arts – Djerba; Judaïsme – Djerba

Tête de femme (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Vieillard accroupi (La Griba, Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Vieillard assis (La Griba, Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Vieux rabbins au gilet rouge assis (Djerba) - Lellouche, Jules (1929)
Dans le Salon Tunisien de 1929
tex.entrytype: artwork
Keywords: Arts – Djerba; Judaïsme – Djerba

Les Israélites de Djerba (Tunisie) (Archives israélites, 1924)
Keywords: Judaïsme – Djerba; Recension

Chez les Israélites de Djerba (La Liberté, 1922)
Keywords: Judaïsme – Djerba

Les Incidents de Djerba: 19 février 1924 - 3 mars 1924 - Ouziel, M. (Alliance israélite universelle, 1924)
9 pièces / ‎1‎9‎3 vues
Keywords: Judaïsme – Djerba

The Jews of Africa : especially in the sixteenth and seventeenth centuries - Mendelssohn, Sidney (Kegan Paul International, 1920)
Jerba, 59, 60, 64, 91, 92, 94, 104 Djado, 59, 65, 66 Djebel Nefoussi, 59, 60, 64, 65, 66, 78
Keywords: Judaïsme – Djebel Nefousa; Judaïsme – Djerba

Zeraʿ ha-shalom - Gatto, Jacob ben Shalom (1920)
Midrashic and homiletical notes on the Pentateuch. Followed by notes on various relgious topics arranged alphabetically.
Keywords: Judaïsme – Djerba

Ṿe-lavash ha-Kohen. Ḳishuṭe kalah - Cohen, Abraham (1927)
Notes on various tractates of the Mishnah. Followed by liturgical poems; and Seder ha-Matslain, prayers for the sick
Keywords: Judaïsme – Djerba

Synagogue and Mosque - Golding, Louis (The Menorah Journal, 1927)
Keywords: Judaïsme – Djerba

Lotus and manna - Golding, Louis (The Menorah Journal, 1926)
Keywords: Judaïsme – Djerba

Chez les Juifs de Djerba. Notes de voyages (suite) - Vitalis, Danon (L'Univers Israélite, 1926)
Keywords: Judaïsme – Djerba

Chez les Juifs de Djerba. Notes de voyages - Vitalis, Danon (L'Univers Israélite, 1926)
Keywords: Judaïsme – Djerba

La Gheriba de Djerba - Benattar, S. C. (La vie tunisienne illustrée, 1924)
Keywords: Judaïsme – Djerba

Sefer Magen Ha-Dat/ Maghen Haddath suivi de "Olam Cattan" - Azoulay, Hanania-Habib (Imprimerie Africaine, 1925)
Djerba/Tunis: David Aydan (David Idan)/ Imprimerie Africaine A. Hadida, 1925. First edition. Hardcover. fair to vg. Octavo. 59pp. 11 double-sided leaves, 16pp. Half tan cloth over red mottled paper boards. Includes both Hebrew and French title pages on either end of the book block, which has both Hebrew (left to right) and Arabic numeral pagination (right to left). Indecipherable inscription in ink on the front free endpaper. The publication includes two separate works. The first is an analysis of and guide to the laws of halizah (Chalitzah) pertaining to the Jewish laws of levirate marriage (know as yibbum), written by prominent Casablanca Rabbi Hanania-Habib Azoulay (or Azulai/ Azulay). The second work is titled "Olam Cattan" (a play on the phrase "small world"), and is the transcript of the Elihu Cattan's memorial speech delivered on the occasion of the death of his father, prominent philanthropist and member of the Tunisian Jewish community Yehuda Cattan. Included is an approbation by Chief Rabbi of Tunisia, Moshe Sitruk (1846-1928). The final 16 pages on the other side of the book block contain an abridged translation of Magen Ha-Dat, as well as the preface and the approbation, in French. Hebrew text in Rashi script, with French. Binding with some rubbing and fraying to extremities. Scratches and abrasions to the covers. A large chip on one of the covers shows the brown cardboard under the paper. Binding reinforced at the gutter of the interior front cover with japan tissue. Binding in fair, interior in very good condition overall. Quite scarce. Protected by modern mylar. David Idan (1873-1955) was a Rabbi, writer and printer, of the prominent Idan family of Tunisian Jews. He served as President of the Djerba Jewish community, and founded the first Hebrew printing press there, in 1912. Hebrew title:ספר מגן הדת. חוברת ראשונה. ונלוה אליו קונטרס עולם קטן אשר הקדש לזכרון יהודה הקטן ע״י בנו אליהו הקטן נדפס ב ג'רבה, תרפ"ה Sefer Magen Hadat.
Keywords: Judaïsme – Djerba

Ohev Mishpat [bound with] Yeled Eliyahu - Allush, Faragi (J. Haddad, 1926)
Djerba: J Haddad. 1926. First Edition. Hardcover. First edition. Period boards. 8vo. 130 pages, 28 pages. 19 cm. Titles translate to "Lover of the Law" and "Child of Eliyahu. " Rabbi Faraji Allush (1854-1921) was born in Gabes, Tunisia. He began his rabbinical career as a rabbi and member of Tunisia's rabbinical court. He would later go on to become the chief rabbi of Djerba and head of Tunisia's rabbinical court (av beit din) . SUBJECTS: Responsa Rabbinics Mizrahim.
Keywords: Judaïsme – Djerba